BESARAN FEE AUDIT PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Evlin Adelina Sinaga; Sistya Rachmawati (Media Riset Akuntansi, Auditing & Informasi, 2018)
This study to examnine the factors that may affect the determination of the independence audit fees on companies listed in Indonesia Stock Exchange (IDX) during 2012-2016 period. The sample collection purpossive techniques so that 92 company obtained as the sampling method of sample. Use the method multiple linear regressiom analysis to analyze the  status of the audit firm , loyality, audit report lag, industry type, the existence of subsidiary, and type of ownership of the company of agains who audit fees formerly data first tested with classical test. The result showed that the satatus of the audit firm , a subsidiary and type of ownership have a significant positive in the determination of audit fees. While the variabel loyality, audit report lag and industry type does not have significant effect on audit fees.